Enhancing Performance of Disadvantaged Pupils through Motivation - Tripathi, K.N. (INDIAN EDUCATIONAL REVIEW, 2015)
Human factors play an important role in the overall development of the individual. In a society like India, where opportunities and privileges are not equally distributed, it becomes necessary to discover the extent of psychological factors that could enhance the performance of individuals irrespective of class, culture, creed or economic status. In the recent past, the study of psychological consequences of poverty, social disadvantaged and deprivation has received considerable attention of researchers. Motivation has emerged as a highly crucial variable in boosting and directing, especially school children towards the achievement of their academic goals. Unlike, privileged individuals, pupils from disadvantaged background lag behind their counterparts in educational attainment. Poor self concept, low achievement motivation, high level of anxiety, high neuroticism, poor performance, and externalisation of success and internalisation of failures are frequently noted in these groups. Against this backdrop, present study aimed to understand certain important aspects of motivation among the socially and culturally disadvantaged and deprived groups of students. In particular the study focused on the question of motivation in the context of human learning and performance.